ANALISIS PENERAPAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 TERHADAP PERTUMBUHAN JUMLAH WAJIB PAJAK DAN PENERIMAAN PPH PASAL 4 AYAT (2) - Dunggio, Jelly Anggraeni; Elim, Inggriani; Mawikere, Lidia (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
The Government through the Directorate General of Taxation has stipulated Government Regulation (PP) Number 46 Year 2013 concerning Tax on MSMEs. In helping small and medium economic activities, the government provides tax services for the UMKM Taxpayers with a 1% tax rate charged on the gross sales cycle of up to Rp 4.8 billion per year. This study aims to explain the growth of the number of taxpayers, before and after the application of PP. No. 46 Year 2013, also aims to explain the acceptance of Income Tax Article 4 Paragraph (2) in the working area of KPP. Pratama Luwuk. This research uses descriptive qualitative analysis method. The results of this study indicate that after the application of PP. No. 46 Year 2013 has decreased the growth of taxpayers by -2.43%, while the average income tax Article 4 Paragraph (2) from PPh UMKM for forty-two months since the implementation of PP. No. 46 Year 2013 is 2.58% with Very Less criteria. In the future, the government especially KPP Pratama Luwuk must be more active and keen in exploring the potential of tax revenue and maintain performance in managing tax revenue, and to evaluate the implementation of PP.No. 46/2013 as the next policy review.Keywords: Government regulation No.46 of 2013, income tax, receipt.